Implementasi Permainan Tradisional Batok Kelapa Untuk Meningkatkan Kemampuan Koordinasi Gerak dan Keseimbangan Tubuh - Nanda Agil Bagus Wicaksono; Anung Priambodo; Marsudianto Marsudianto (Journal of Creative Student Research, 2024)
This research aims to improve the movement coordination and body balance abilities of class 1C students at SDN Pakis 1 Surabaya through the implementation of the traditional coconut shell game. This Classroom Action Research (PTK) was carried out in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The results showed a significant improvement in students' motor skills. At pre-cycle, only 25% of students achieved the expected skills. After implementing the coconut shell game, the percentage of students who completed it increased to 42.86% in the first cycle and 82.14% in the second cycle. This increase indicates that the traditional coconut shell game is an effective method in developing students' movement coordination and body balance skills and providing a fun and active learning experience.